Wahbah Zuhaily on Riqāb: Reshaping its Implementation in South Sulawesi - Husain, Hukmiah; Makkarateng, Ma'adul Yaqien; Arafah, Muh.; Hasan, Hamsah (Universitas Darussalam Gontor, 2024)
This article examines the contemporary interpretation of riqāb (emancipation of slaves) as a category for zakat recipients, as articulated by Wahbah al-Zuḥaylī, a prominent Islamic jurist. While slavery is no longer a widespread institution, al-Zuḥaylī's reinterpretation of riqāb holds significant implications for addressing modern social issues, particularly those related to poverty and marginalization in South Sulawesi. The study explores potential avenues for zakat distribution to support initiatives that align with the essence of riqāb, such as education, skill development, and debt relief. By applying al-Zuḥaylī's perspective, this research contributes to a broader understanding of zakat's role in social upliftment in the region. This research adopts a qualitative approach, relying primarily on textual analysis and interpretation of al-Zuḥaylī's jurisprudence regarding zakat and riqāb. Secondary sources, including academic articles, reports, and policy documents, are also employed to contextualize the findings within the socioeconomic landscape of South Sulawesi. Reinterpreting the Islamic concept of riqāb in the modern context offers profound implications for both Islamic thought and contemporary society, facilitating a more inclusive and dynamic understanding of zakat’s potential to address pressing social challenges.